Urinary albumin excretion from spot urine samples predict all-cause and stroke mortality in africans - Schutte, Rudolph; Schmieder, Roland; Huisman, Hugo W.; Smith, Wayne; Van Rooyen, Johannes M.; Fourie, Carla M. T.; Kruger, Ruan; Uys, Lisa; Ware, Lisa; Mels, Catharina M. C.; Greeff, Minrie; Kruger, Iolanthe M.; et al. (American Journal of Hypertension, 2014)
Increased urinary albumin excretion reflects general vascular damage and predicts adverse cardiovascular and renal outcomes. Albuminuria can be determined from easily collected spot urine samples, especially in low-resource settings. However, no prognostic evidence exists for Africans.We followed clinical outcomes in 1,061 randomly selected non diabetic, human immunodeficiency virus (HIV)-negative Africans (mean age: 51.5 years; 62.0% women). Baseline urinary albumin-to-creatinine ratio was assessed from spot urine samples.Over a median follow-up of 4.52 years, 132 deaths occurred, of which 47 were cardiovascular related. The urinary albumin-to-creatinine ratio averaged 6.1 ?g/mg (5th to 95th percentile interval; 1.2-70.0). In multivariable-adjusted analyses, urinary albumin excretion predicted all-cause mortality (hazard ratio (HR), 1.26; 95% confidence interval (CI), 1.07-1.48; P = 0.006), and a tendency existed for cardiovascular mortality (HR, 1.26; 95% CI, 0.97-1.63; P = 0.087), which seemed to be driven by fatal stroke (HR, 1.72; 95% CI, 1.17-2.54; P = 0.006) rather than cardiac mortality (HR, 0.67; 95% CI, 0.41-1.07; P = 0.094). The predictive value remained in 528 hypertensives for both all-cause (HR, 1.38; 95% CI, 1.13-1.69; P = 0.001) and cardiovascular (HR, 1.45; 95% CI, 1.07-1.96; P = 0.017) mortality, again driven by stroke. Our findings also remained significant after we excluded participants with macroalbuminuria, those on antihypertensive treatment, as well as participants who died within 1 year after enrollment.In nondiabetic HIV-negative Africans, albuminuria predicts all-cause and stroke mortality.
EVALuna2:3675